Corporalidades transgressoras: desafios das transformações corporais de pessoas transgênero no contexto da Política Social de Saúde na Colômbia - Espitia-Pachón, Natália (2017)
The body transformations are part of the health and the free development of the personality of the transgender population, who experience an identity that problematizes the gender imposed from the biological characteristics and constructs their identity according to their desire of being able to be man, woman or both at the same time. The objective of this research, is to analyze the challenges of the transgender population transformation of the city of Bogotá from the prospect of the Social Policy of Health in Colombia. The main paradigm that we used in this research is genealogical-archaeological. As a result, it was identified that the foremost challenges of the transgender population related to their corporal transformations in the context of health correspond to the absence of public policies that guarantee their rights and their needs, the lack of studies and information related to this theme. This paperwork also points out that the structure of the Health System is influenced by the neoliberal ideology dismantling accomplished universal rights and transforms human life into a merchandise, in this sense, health care is limited to a package of services where the body transformation procedures are not included, except for Of people who have the certificate of gender dysphoria, which implies recognizing that they have an identity disorder. However, not all people are certified dysphoria because of difficulties in accessing the Health System, and not all of those that have the chance to be evaluated by the psychiatrist obtain the certificate accordingly the various economic, pathological, bureaucratic, and restrictive barriers generate the isolation of the transgender population with the Health System, a fact that leads these social subjects to seek alternative procedures for their corporal transformations, often putting their lives at risk. Likewise, the consequences of these processes are not assumed by the Health System, a decision backed by the judiciary that states that it is the sole responsibility of the person thereby denying the responsibility of the State in this situation.